Emerging research trends in medical textiles - Gokarneshan, N.; Rachel, D. Anitha; Rajenn, V.; Lavanya, B.; Ghoshal, Arundhathi; SpringerLink (Online service). (Singapore Springer Singapore, 2015)
This book provides a comprehensive review of the significant researches reported during the recent years in the field of medical textiles. It also highlights the use of new types of fibers in developing medical textile products and their promising role in the respective areas of application. Considerable developments have taken place in the development of medical textiles for varied applications.
Introduction -- Wound Dressings from Nano Fibre Matrix of Calcium Alginate/PVA Blend -- Membrane Coated Cotton Wound Dressings -- PLA Knitted Scaffold -- Non Woven Scaffolds for Improved Cell Growth -- Phosphorylated Cotton Chronic Wound Dressing -- New Orthopaedic Support Material -- Studies on PET Implants for Long Term Durability -- Ammonia Plasma Treatment of Viscose Wound Dressings -- Tencel /Gelatin Composite Wound Dressing -- Smart Shape Memory Fabric ? Biological Evaluation -- Textile Heart Valve Prosthesis? Influence of Fabric Parameters on Durability.
Electronic reproduction.
Keywords: Nonwoven fabrics in medicine; Biomedical materials; Textile fabrics; Electronic books